2006
DOI: 10.1112/s0024610706022629
|View full text |Cite
|
Sign up to set email alerts
|

The Parity Problem for Reducible Cubic Forms

Abstract: Let f ∈ Z[x, y] be a reducible homogeneous polynomial of degree 3. We show that f (x, y) has an even number of prime factors as often as an odd number of prime factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 21 publications
1
11
0
1
Order By: Relevance
“…We remark that this conjecture was also recently verified for all homogeneous polynomials of degree at most three in [27], [28]. Removing the homogeneity assumption looks hopeless with current technology; the case P .y 1 ; y 2 / D y 1 .y 1 C 2/ is already roughly of the same order of difficulty as the twin prime conjecture.…”
Section: Correlation Estimates For Möbius and Liouvillesupporting
confidence: 56%
“…We remark that this conjecture was also recently verified for all homogeneous polynomials of degree at most three in [27], [28]. Removing the homogeneity assumption looks hopeless with current technology; the case P .y 1 ; y 2 / D y 1 .y 1 C 2/ is already roughly of the same order of difficulty as the twin prime conjecture.…”
Section: Correlation Estimates For Möbius and Liouvillesupporting
confidence: 56%
“…Helfgott has shown that the root number in this family is equidistributed [He2]. We have the following.…”
Section: Curves With Prescribed Torsionmentioning
confidence: 87%
“…A variant of Chowla's conjecture. A classical conjecture of Chowla [9] states that if λ is the Liouville function and P ∈ Z[x, y] is a homogeneous polynomial such that P = cQ 2 for every c ∈ Z, Q ∈ Z[x, y], then This was established by Landau when deg(P ) = 2 [52] (see also [39]), by Helfgott when deg(P ) = 3 [40,41], and when P is a product of pairwise independent linear forms by Green, Tao, and Ziegler [29,30,31,32]. The conjecture is also closely related to the problem of representing primes by irreducible polynomials, for relevant work see [16,36,37,38].…”
mentioning
confidence: 99%